2019
DOI: 10.5296/jbls.v11i1.15459
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Toxicity of Carisoprodol Drug (Somadril Compound) on Pulmonary Tissues of Albino Rats

Abstract: Carisoprodol is a common muscle relaxant indicated as adjunctive therapy in acute, painful musculoskeletal cases. This current study aimed to investigate the histopathological, histochemical and immunohistochemical effects in the lung tissue of the pregnant rats and their fetuses after carisoprodol treatment. The present study was applied on twenty seven pregnant female rats and they were randomly divided into three groups (nine pregnant female rats in each group). Rats of the first (control) group were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In a previous study,carisoprodol treatment of the pregnant rats caused severe variations in the esophageal tissue of fetuses such as : highly thickened mucosal layers with lots of vacuolated cells and highly distorted submucosal layer, discontinuous and ruptured muscle fibres in the muscularis after administrated of carisoprodol (7) . Also, lung of treated rats with somadril showed congested alveolar septa, highly congested blood vessels which contained haemolysed blood cells,highly thickened alveolar septa, reduced alveolar sacs with thickened and corrugated epithelial layer of the bronchioles (8) .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a previous study,carisoprodol treatment of the pregnant rats caused severe variations in the esophageal tissue of fetuses such as : highly thickened mucosal layers with lots of vacuolated cells and highly distorted submucosal layer, discontinuous and ruptured muscle fibres in the muscularis after administrated of carisoprodol (7) . Also, lung of treated rats with somadril showed congested alveolar septa, highly congested blood vessels which contained haemolysed blood cells,highly thickened alveolar septa, reduced alveolar sacs with thickened and corrugated epithelial layer of the bronchioles (8) .…”
Section: Introductionmentioning
confidence: 95%
“…These investigations agree with those of Abouel-Maged (9) , Anwar et al (10) and Ali et al (28) who found that treated adult male rats with somadril at 200 mg/kg led to destruction of the histological architecture of the seminiferous tubules, testicular vacuolation and degeneration and reduced spermatozoa within the lumen of the testis. Treatment of carisoprodol at doses 10.8 and 21.6 mg/kg caused degenerative changes in the lung, esophagus and liver tissues of the pregnant rats and their fetuses (7)(8)(9) .…”
Section: Skinmentioning
confidence: 99%
See 1 more Smart Citation